The Burden of Care: A National Survey on the Prevalence, Demographic Characteristics and Health Problems Among Young Adult Carers Attending Higher Education in Norway - Haugland, Bente Storm Mowatt; Hysing, Mari; Sivertsen, Børge (Frontiers in Psychology, 2020)
Objective: The aim of the present study was to examine prevalence, characteristics and health outcomes among young adults (18 to 25 years) who provide informal care to family members or others with physical or mental illnesses, substance misuse or disabilities. Design: The sample was obtained from a national survey in Norway from 2018 among students in higher education (the SHoT2018-study). The current sample comprise 40,205 participants, 70.2% women, mean age 22 years (SD=1.7). Outcome Measures: Participants answered questions on care responsibilities, mental health problems (The Hopkins Symptoms Checklist-25), insomnia (sleep questionnaire), somatic health (Somatic Symptom Scale-8) and life satisfaction (Satisfaction With Life Scale). Results: 5.5% of the respondents reported having care responsibilities. Caring was associated with being female, single, having divorced parents, being an immigrant, and having financial difficulties. More mental health problems, insomnia, and somatic symptoms, and lower life satisfaction were found among respondents with care responsibilities. Number of hours of caring was associated with negative health outcomes in a dose-response pattern. Conclusion: Professionals within health care, social services and the educational system should be sensitized to the needs of young adults with care responsibilities for family members or others with illness, substance misuse or disabilities. The negative health problems among these young adult carers should be acknowledged, and adequate support made available.